Procedencia y emergencia del discurso sobre la inferioridad del indio y sus efectos en el presente - Méndez Medina, Marcelo (2025)
In many texts written during the 16th century, both by those who were protagonists of the Conquest of Mexico-Tenochtitlan and by those who were not, they talk about the nature of the inhabitants of these lands, as well as their moral quality, form of life and practicing religion. Some of the objectives of such texts were to show the Old World the culture of the Nahuas, Mayans, Purépechas, among other indigenous groups, at the same time that they judged it as inferior, for ignoring, among other things, the Christian religion. Where can the descent and emergence of the discourse on the inferiority of human beings who lived in these lands before the arrival of “Western Christian humanism” be located and what effects does said discourse have in the present in the formation of some current forms of subjectivity? This is what I try to resolve in this text.